An assessment of the nutritional status of a school-aged population from Argelia, Colombia - Ortega Bonilla, Rubén Andrés (2018)
Malnutrition affects most rural areas in Colombian, mainly involving the school-aged population. The aim of this study was to assess the nutritional status of students (n=1,528) attending an Agricultural College in the town of Argelia in south-western Colombia in the Cauca department. Methods The school-aged children’s weight and height were measured and their nutritional status was determined from their body mass index (BMI), according to criteria defined by the World Health Organization (WHO). Anthropometric measurements were analyzed by means of measures of central tendency, stratified by gender and age. The standard error of the difference was estimated to specify the statistical significance of some of the most important differences observed between study indicators; such significance was verified at 0.05 level. Results Prevalence regarding malnutrition and thinness in 5-10 years-old children, a trend towards obesity in adolescents and growth retardation in children and adolescents was established from analysis of the children’s weight (P/E), height for age (H/A) and BMI. Conclusions The results suggested that sports should be encouraged at an early age, as well as training school children and their families regarding healthy eating habits and thus provide scientific support for planning government healthcare agencies’ prevention and control strategies.